Military dune buggies - Green, Michael (Mankato, Minn. : Capstone Press, 1997)
Discusses the history and use of military dune buggies, highlighting specific models and their roles in various battles.
Includes bibliographical references and index.
860L
Keywords: Desert patrol vehicle -- Juvenile literature; Desert patrol vehicle